2014
DOI: 10.1007/s11046-014-9778-9
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Characterization of Candida nivariensis from a Culture Collection of Candida glabrata Clinical Isolates in Malaysia

Abstract: This study reports for the first time the emergence of C. nivariensis in our clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 27 publications
0
16
0
1
Order By: Relevance
“…2008 , Lockhart et al 2009 , Chowdhary et al 2010 , Gorton et al 2013 , López-Soria et al. 2013 , Sharma et al 2013 , Li et al 2014 , Swoboda-Kopeć et al 2014 , Tay et al 2014 , Feng et al 2015 ), 55 isolates of C. nivariensis have been described in 35 cases in European countries, 19 cases in Asia, and one case report in Australia ( Table I ). Therefore, there are no cases of C. nivariensis in the American continent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2008 , Lockhart et al 2009 , Chowdhary et al 2010 , Gorton et al 2013 , López-Soria et al. 2013 , Sharma et al 2013 , Li et al 2014 , Swoboda-Kopeć et al 2014 , Tay et al 2014 , Feng et al 2015 ), 55 isolates of C. nivariensis have been described in 35 cases in European countries, 19 cases in Asia, and one case report in Australia ( Table I ). Therefore, there are no cases of C. nivariensis in the American continent.…”
Section: Resultsmentioning
confidence: 99%
“…MALDI-TOF analyses were later demonstrated to be an efficient tool to differentiate these species ( Gorton et al 2013 ). Since then, other cases have been reported in Europe ( Borman et al 2008 , Gorton et al 2013 , López-Soria et al 2013 , Swoboda-Kopeć et al 2014 ), Asia ( Fujita et al 2007 , Wahyuningsih et al 2008 , Chowdhary et al 2010 , Sharma et al 2013 , Li et al 2014 , Tay et al 2014 , Feng et al 2015 ), and Australia ( Lockhart et al 2009 ). The total number of C. nivariensis isolates described in the literature has been low in these countries.…”
mentioning
confidence: 99%
“…On the other hand, some clinical isolates of C. nivariensis recovered from blood [23] and vaginal swabs [24] showed high MIC values for FLC and infected patients were not responsive to this drug. Data derived from the literature review revealed that there is a strain and geographical variability for antifungal susceptibility patterns of isolates of C. nivariensis and it seems that this phenomenon is common for clinical isolates of C. glabrata, as well [15,25]. Although, one of our patients that was treated with CSP plus FLC and AMB deoxycholate survived, unfortunately no data was available on his follow-up to ensure that he is alive.…”
Section: Variability In Antifungal Susceptibility Patterns and Clinicmentioning
confidence: 90%
“…The panfungal PCR and sequencing advantage is that this technique allows the identification of cryptic species or complex species, but it is recommended to combine the amplification of the D1/D2 region with other targets in the ITS region 24 , 26 . In this report, although the presence of cryptic species of Candida parapsilosis and Candida glabrata were not observed, it is important to use methodologies that are able to detect them, mainly due to the emergence of species that are difficult to manage 9 , 37 , 38 . In addition, this technique would be the best option, despite its cost, for those identifications that are doubtful or where other methodologies have low discriminatory power.…”
Section: Discussionmentioning
confidence: 88%
“…La ventaja de la PCR panfungal y secuenciación radica en que esta técnica permite identificar especies crípticas o complejos de especies, pero se recomienda combinar la amplificación de la región D1/D2 con otros blancos en la región ITS 24 - 26 . En este trabajo, aunque no se observó la presencia de especies crípticas de Candida parapsilosis y Candida glabrata , es importante tener en cuenta la importancia de emplear metodologías que sean capaces de detectarlas, debido principalmente a la emergencia de especies con perfiles de sensibilidad de difícil manejo 9 , 37 , 38 . Además, sería la mejor opción, a pesar de su costo, para aquellas identificaciones que por otras metodologías generen identificaciones dudosas o con bajas discriminaciones.…”
Section: Discussionunclassified